School curriculum and educational equity - Montero Alcaide, Antonio (Avances en Supervisión Educativa, 2025)
Equity, as a principle of the education system, affects its main areas, such as the curriculum. Hence, the opportunity to link curriculum and equity, in connection with the participation in the 17th State Congress on Education Inspection of the Association of Education Inspectors (ADIDE), "Equity, Equality, and Educational Inspection," held in Córdoba in November 2024. Four aspects are, therefore, of interest: educational equity in the different theories of curriculum; prescribed curriculum design models and the equitable adaptation of teaching; equity and basic education in the education system; as well as the influence of curriculum presentations, teachers’ expectations of students, and the paradigm of social justice. These issues are significant in order to provide some ideas and reflections on their contribution to equity. This, as a general conclusion, must seek equal educational opportunities for academic success, completely opposed to the inequitable reproduction of personal and social inequalities of origin, achieving equal opportunities for access to education, but without adequate educational responses, mainly in compulsory education.